Homeownership and Unemployment: The Effect of Market Size - Taskin, Ahmet; Guler, Bulent (Labour Economics, 2018)
This paper explores the effects of local labor market size on the unemployment hazard rate differential between renters and homeowners. Through a partial labor search-theoretic model, by explicitly modeling renters and owners, we find an asymmetric effect of the local labor market size on the unemployment hazard rate difference between renters and homeowners. We show that homeownership introduces additional frictions into the labor market especially when the local labor market is weak. We also show that these additional frictions make homeowners less mobile, and they become less likely to accept outside job offers, and more likely to accept local offers. Using data from the Survey of Income and Program Participation (SIPP), we find empirical evidence for the theoretical predictions of the model: (i) as local labor market opportunities deteriorate, homeowners become more likely to remain unemployed, (ii) homeowners have lower post unemployment wages than renters in local labor markets.<br